If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(t + -7) = 6 Reorder the terms: 2(-7 + t) = 6 (-7 * 2 + t * 2) = 6 (-14 + 2t) = 6 Solving -14 + 2t = 6 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 2t = 6 + 14 Combine like terms: -14 + 14 = 0 0 + 2t = 6 + 14 2t = 6 + 14 Combine like terms: 6 + 14 = 20 2t = 20 Divide each side by '2'. t = 10 Simplifying t = 10
| ((7p^5q^2)/(9n^4))/((21p^3q)/3mn^2)) | | 6=2(c-3) | | 7(1+5n)-8(6a+5)=32 | | 8x+4=2x+136 | | 3,2+2,6=x | | [5/(3x^3-2x^2-5)]=[2/(x^3-2)] | | 499=d+403 | | 2as=vf^2-vi^2 | | 44=p-180 | | y^2=8y-16 | | U+46=95 | | X=r+dt | | cos(tan^(-1)(3/4)-π/2) | | -v=-34 | | g-67=-5 | | 75=p-6 | | X^2-3x+3=-k | | 0.5x+42=6.5 | | 8r=9r-r | | -5j=8-5j | | 3(s+1)-(s-1)2=10-(5-3s) | | y=0.5x^2-6x+13 | | 4x^2-3x+7=9x+27 | | 3a+ab=14+x | | 2y+-10=8 | | x-8[8/9]=6/7 | | 3u-7=2 | | 3(2y+5)=2(5y-2) | | 6x-15=5x+4 | | 2x^2+4xy+3y^2-4x=7 | | 4x(-3x-5)= | | -2/7u=-12 |